(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: A stroke is a sudden focal neurological deficit resulting from a vascular lesion. Symptoms typically last longer than 24 h if the patient survives. Citicoline, an abbreviation of cytidine-5’- diphosphocholine, is an endogenous chemical compound. It can be bought as a tablet or an injection. Citicoline, also known as cytidine diphosphate choline, is a crucial pyrimidine 5’-nucleotide that plays a significant role in the body’s biochemical processes. It serves as an essential pre-cursor in the synthesis of lecithin, or phosphatidylcholine, which is vital for maintaining cellular membrane integrity and fluidity. Moreover, research suggests that citicoline may have neuroprotective properties, potentially aiding recovery in conditions such as stroke and cognitive decline. Citicoline has comprehensive neuroprotective properties. Materials and Methods: The study was performed in 80 patients with stroke. Fifty patients received citicoline and the remaining 30 patients did not receive citicoline. The changes in activities of daily living (ADL) and degree of disability were measured using the Barthel index (BI) and Modified Rankin Scale (mRS), respectively. All statistical analyses were carried out using post hoc analysis. Results and Discussion: Males were predominant in our study. The predominant age group for developing ischemic stroke was found to be 51–65 years. The common symptoms associated with stroke were found to be slurring of speech (18.2%), right hemiparesis (13.5%), giddiness (9.4%), and left hemiparesis (8.8%). Hypertension and diabetes mellitus have been identified as the most common comorbidity associated with stroke. Conclusion: On comparing the BI and mRS of the stroke patients, clinically there is a significant improvement in ADL, cognitive functions, and functional ability of both the test and control group. On screening the patients for safety measures, no adverse event has been reported.